Phospholipolysis Caused by Different Types of Bacterial Phospholipases During Cold Storage of Bovine Raw Milk Is Prevented by N2 Gas Flushing - Munsch-Alatossava, Patricia; Käkelä, Reijo; Ibarra, Dominique; Youbi-Idrissi, Mohammed; Alatossava, Tapani (Frontiers in Microbiology, 2018)
Cold storage aims to preserve the quality and safety of raw milk from farms to dairies; unfortunately, low temperatures also promote the growth of psychrotrophic bacteria, some of which produce heat-stable enzymes that cause spoilage of milk or dairy products. Previously, N2 gas flushing of raw milk has demonstrated significant potential as a method to hinder bacterial growth at both laboratory and pilot plant scales. Using a mass spectrometry-based lipidomics approach, we examined the impact of cold storage (at 6°C for up to 7 days, the control condition (C)), on the relative amounts of major phospholipids (phosphatidylethanolamine/PE, phosphatidylcholine/PC, phosphatidylserine/PS, phosphatidylinositol/PI and sphingomyelin/SM) in three bovine raw milk samples, and compared it to the condition that received additional N2 gas flushing (N). As expected, bacterial growth was hindered by the N2-based treatment (over 4 log-units lower at day 7) compared to the non-treated control condition. At the end of the cold storage period, the control condition (C7) revealed higher hydrolysis of PC, SM, PE and PS species (the major species reached 27.2, 26.7, 34.6, 9.9 μM, respectively), compared to the N2-flushed samples (N7) (the major species reached 55.6, 35.9, 54.0, 18.8 μM, respectively). C7 samples also exhibited a 3-fold higher phosphatidic acid (PA) content (6.8 μM) and a 5-fold higher content (17.3 μM) of lysophospholipids (LPE, LPC, LPS and LPI) whereas both lysophospholipids and PA remained at their initial levels for 7 days in N7 samples. Taking into consideration the significant phospholipid losses in the controls, the lipid profiling results together with the microbiological data suggest a major role of phospholipase (PLase) C (PLC) in phospholipolysis during cold storage. However, the experimental data also indicate that bacterial sphingomyelinase C, together with PLases PLD and PLA contributed to the degradation of phospholipids present in raw milk as well, and potential contributions from PLB activity cannot be excluded. Altogether, this lipidomics study highlights the beneficial effects of N2 flushing treatment on the quality and safety of raw milk through its ability to effectively hinder phospholipolysis during cold storage.